Kinetics and Mechanism of Induced Oxidation Reaction of Iodide by Chromate. - AMPILY, J.S.; SOLANKI., S.K. (Asian Journal of Chemistry, 2010)
The induced oxidation reaction of iodide by chromate has been studied, In this chromate-iodide reaction, chromate acts as an oxidant, iodide as acceptor and iron(II) as inductor. The reaction takes place in acid medium. From the observation and findings, the rate law obtained is as follows.